Effects of supplement amount, with or without calcium salts of fatty acids, on growth performance and intake behavior of grazing Bos indicus bulls - Cappellozza, Bruno I (Transl Anim Sci, 2020)
This study evaluated the effects of 2 supplement dry matter (DM) amounts, with or without calcium salts of fatty acids (CSFA), on growth performance, supplement and water intake behavior of grazing beef bulls. On day 0, 32 Nellore bulls were ranked by initial body weight (BW; 318 ± 11.2 kg), and then, randomly assigned to treatments (n = 8 bulls/treatment), in a 2 × 2 factorial design, which consisted of energy-based supplement DM amount of 0.3 (SP03) or 1.0 (SP1) % of BW with (+) or without (−) CSFA fortification (90 to 100 g/bull daily). During the experiment (98 d), all bulls were managed as single group and rotated between 2 Brachiaria pastures every 9 to 11 d. Each pasture contained an individual electronic data capture system with 2 feed bunks/treatment and 1 water through to determine individual supplement DM and water intake, as well number of visits, time spent at the feeder/waterer, and intake per visit (IPV). A supplement effect was detected (P = 0.02) for final BW. Bulls supplemented at 1.0% of BW, regardless of CSFA inclusion amount, were heavier at the end of the experiment vs. SP03 bulls. Overall average daily gain (ADG) was greater (P = 0.05) for SP03+ vs. SP03− bulls, and did not differ (P = 0.87) between SP1+ vs. SP1− bulls. No supplement amount, CSFA, or supplement amount × CSFA effects were observed (P ≥ 0.13) for supplement and water intake behavior, number of visits to the feeder or IPV. However, SP1 bulls spent (P = 0.05) more time at the feeder than SP1+ bulls, whereas bulls supplemented with CSFA tended (P = 0.10) to consume less water (as % of BW) than cohorts supplemented without CSFA. In summary, CSFA fortification into 0.3% of BW supplements increased ADG when compared with cohorts not offered CSFA. On the other hand, no benefits were observed when CSFA was included into 1.0% of BW supplements, primarily due to the lower than projected supplement, and consequently, CSFA intake. Moreover, CSFA fortification tended to reduced water intake, demonstrating a potential of this technology to increase performance of beef herds, while maintaining the utilization of natural resources.